The NO/cGMP pathway inhibits transient cAMP signals through the activation of PDE2 in striatal neurons - Polito, Marina; Klarenbeek, Jeffrey; Jalink, Kees; Tritsch, Danièle; Vincent, Pierre; Castro, Liliana R. (Frontiers in Cellular Neuroscience, 2013)
The NO-cGMP signaling plays an important role in the regulation of striatal function although the mechanisms of action of cGMP specifically in medium spiny neurons (MSNs) remain unclear. Using genetically encoded fluorescent biosensors, including a novel Epac-based sensor (EPAC-SH150) with increased sensitivity for cAMP, we analyze the cGMP response to NO and whether it affected cAMP/PKA signaling in MSNs. The Cygnet2 sensor for cGMP reported large responses to NO donors in both striatonigral and striatopallidal MSNs, and this cGMP signal was controlled partially by PDE2. At the level of cAMP brief forskolin stimulations produced transient cAMP signals which differed between D1 and D2 medium spiny neurons. NO inhibited these cAMP transients through cGMP-dependent PDE2 activation, an effect that was translated and magnified downstream of cAMP, at the level of PKA. PDE2 thus appears as a critical effector of NO which modulates the post-synaptic response of MSNs to dopaminergic transmission.